1997
DOI: 10.1046/j.1365-2265.1997.1270942.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone responses to GH‐releasing peptide (GHRP‐6) in hypothyroidism

Abstract: We have shown that patients with primary hypothyroidism have higher GH responses to GHRP-6 than to GHRH, which are markedly blunted. When GHRP-6 was associated with GHRH, a significant increase in the GH response was observed in these patients, which could suggest a role for somatostatin in this process. Our data suggest that thyroid hormones modulate GH release induced by GHRH and GHRP-6 through different mechanisms. However, additional studies are necessary to further elucidate this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 41 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…It has previously been suggested that thyroid hormones could modulate intracellular mechanisms in the somatotroph ( Ramos‐Dias et al ., 1996 ; Pimentel‐Filho et al ., 1997 ). It has recently been demonstrated that hyperthyroid patients have a normal GH response to GHRP‐6 associated with a blunted GH response to GHRH ( Ramos‐Dias et al ., 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been suggested that thyroid hormones could modulate intracellular mechanisms in the somatotroph ( Ramos‐Dias et al ., 1996 ; Pimentel‐Filho et al ., 1997 ). It has recently been demonstrated that hyperthyroid patients have a normal GH response to GHRP‐6 associated with a blunted GH response to GHRH ( Ramos‐Dias et al ., 1996 ).…”
Section: Discussionmentioning
confidence: 99%